Evaluation of SWAT-C Model Applicability for TOC Simulation and Analysis of TOC Load Characteristics in the Geumho River Basin - Jeongho Han; Gwanjae Lee (대한환경공학회지)
This study evaluated the applicability of the SWAT-C model for Total Organic Carbon (TOC) simulation on a daily basis in the Geumho River basin and analyzed the spatiotemporal characteristics of TOC loads. Model calibration and validation results showed “very good” performance for streamflow simulation during both calibration (2018-2020) and validation (2021-2022) periods based on R2 and NSE indicators. TOC simulation demonstrated “satisfactory” or better performance for the same periods. However, a tendency to underestimate TOC loads was observed during peak flow events. TOC loads showed a high correlation with precipitation (r = 0.99, p < 0.05) and exhibited distinct seasonal patterns, with the highest loads in summer and the lowest in winter. Analysis of TOC composition revealed that Dissolved Organic Carbon (DOC) accounted for an average of 82% of TOC loads while Particulate Organic Carbon (POC) contributed 18% in the Geumho River basin, with higher POC ratios observed during the fall season compared to other seasons. This study is significant as it represents the first application of daily TOC simulation using the SWAT-C model in the Geumho River basin in Korea, validating the model's applicability and comprehensively analyzing the temporal characteristics of TOC loads. The results provide scientific basis for implementing TOC Total Maximum Daily Load (TMDL) regulations in the Geumho River basin and contribute to developing effective water quality management strategies.